Petrography and geochemistry of the Triassic El Tranquilo Group, Deseado Massif, Patagonia, Argentina: Implications for provenance and tectonic setting. (December 2018) - Jenchen, Uwe
Abstract: The Middle to Late Triassic El Tranquilo Group (El Tranquilo anticline, Deseado Massif, Patagonia) is a key area between coeval West Argentinean and North Patagonian outcrops and of the area of Southwestern Gondwana. The El Tranquilo Group's continental sequence is part of an extensional setting related to the accretion of Patagonia. Petrographic (qualitative and modal) analyses and geochemical analyses (major, trace elements, and rare earth elements (REEs)) of 90 samples were carried out. The sediments of the El Tranquilo anticline are arkoses and lithic arenites containing lithic fragments from felsic volcanic rocks. Polycrystalline quartz, sub-euhedral K-feldspar, and biotite are abundant and corroborate an acidic plutonic source. Major element ratios, trace element ratios (Ti/Nb, Th/Sc, Eu/Eu*), and REE distribution patterns indicate direct derivation from igneous felsic rocks. Paleogeographic constructions locate the El Tranquilo anticline near a Permo-Triassic volcanic arc. Although the input of acidic igneous material to the El Tranquilo sag is clear, the composition of the sandstones could not be confirmed as predominantly volcaniclastic. Thus, petrography could not confirm the extension of Permo-Triassic Choiyoi volcanism to Southern Patagonia, Karoo basin, and Antarctic Peninsula. Low recycling rates indicate short transport distances; considering the time between cooling and exhumation, the most probable dominant source areas are the Late Ordovician Dos Hermanos granitoids, Silurian El Sacrificio granitoids, Devonian Bahía Laura granitoids, or Carboniferous Mina La Leona granitoids. Graphical abstract: Image 1 Highlights: Link between the North Patagonian Massif and the Antarctic Peninsula and Karoo Basin. Volcanic activity of the Permotriassic Arc (Choiyoi) in the Deseado Massif doubtful. Triassic sediments of Deseado Massif derived from Paleozoic granitoids. New approaches to the interpretation of geochemical analyses of clastic sediments. Providing a most complete geochemical dataset for El Tranquilo Group.